An algorithm for simultaneous determination of pressure and temperature distribution in oil-producing tube flow and the counter flow in gas-lift annulus - Hien, Ha Ngoc; Diep, Nguyen Van; Hai, Duong Ngoc; Canh, Nguyen Van (Vietnam Journal of Mechanics, 1999)
An algorithm for simultaneous determination of pressure and temperature distribution in oil-producing tube flow and the counter flow in gas-lift annulus has been proposed. The algorithm is based on a double loop iterative procedure and shooting method. The two-phase flow calculation for pressure Used in the algorithm is based on improved methods of Beggs and Brills, Orkissewski or Hagedorn and Brown. The numerical implementation for an example is presented to assure the applicability of proposed algorithm.